Role of miR-132 in Angiogenesis after Ocular Infection with Herpes Simplex Virus - Mulik, Sachin (American Society for Investigative Pathology, 2012)
MicroRNAs (miRNAs) are small regulatory molecules that control diverse biological processes that include angiogenesis. Herpes simplex virus (HSV) causes a chronic immuno-inflammatory response in the eye that may result in corneal neovascularization during blinding immunopathological lesion stromal keratitis (SK). miR-132 is a highly conserved miRNA that is induced in endothelial cells in response to growth factors, such as vascular endothelial growth factor (VEGF). In this study, we show that miR-132 expression was up-regulated (10- to 20-fold) after ocular infection with HSV, an event that involved the production of both VEGF-A and IL-17. Consequently, blockade of VEGF-A activity using soluble VEGF receptor 1 resulted in significantly lower levels of corneal miR-132 after HSV infection. In addition, low levels of corneal miR-132 were detected in IL-17 receptor knockout mice after HSV infection. In vivo silencing of miR-132 by the provision of anti-miR-132 (antagomir-132) nanoparticles to HSV-infected mice led to reduced corneal neovascularization and diminished SK lesions. The anti-angiogenic effect of antagomir-132 was reflected by a reduction in angiogenic Ras activity in corneal CD31-enriched cells (presumably blood vessel endothelial cells) during SK. To our knowledge, this is one of the first reports of miRNA involvement in an infectious ocular disease. Manipulating miRNA expression holds promise as a therapeutic approach to control an ocular lesion that is an important cause of human blindness.